2015
DOI: 10.1016/j.stemcr.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Conditionally Stabilized dCas9 Activator for Controlling Gene Expression in Human Cell Reprogramming and Differentiation

Abstract: SummaryCRISPR/Cas9 protein fused to transactivation domains can be used to control gene expression in human cells. In this study, we demonstrate that a dCas9 fusion with repeats of VP16 activator domains can efficiently activate human genes involved in pluripotency in various cell types. This activator in combination with guide RNAs targeted to the OCT4 promoter can be used to completely replace transgenic OCT4 in human cell reprogramming. Furthermore, we generated a chemically controllable dCas9 activator ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 36 publications
1
152
0
Order By: Relevance
“…Additionally, dCas9 can inhibit gene expression by simply blocking transcriptional initiation or elongation through a process known as CRISPR interference (Qi et al 2013), although fusing dCas9 to transcriptional repressor domains can also lead to efficient silencing from the promoter Zalatan et al 2015). Much like zinc fingers and TALEs, methods for achieving conditional gene modulation using dCas9 have also been reported, including the fusion of a dihydrofolate reductase destabilization domain to dCas9, which can provide chemical control over activation, enabling cellular reprogramming or differentiation (Balboa et al 2015). Light-inducible dCas9-based systems capable of providing optical control of gene expression provide another means for achieving conditional control of gene expression (Nihongaki et al 2015;Polstein and Gersbach 2015).…”
Section: Targeted Transcription Factors Tools For Modulating Gene Expmentioning
confidence: 99%
“…Additionally, dCas9 can inhibit gene expression by simply blocking transcriptional initiation or elongation through a process known as CRISPR interference (Qi et al 2013), although fusing dCas9 to transcriptional repressor domains can also lead to efficient silencing from the promoter Zalatan et al 2015). Much like zinc fingers and TALEs, methods for achieving conditional gene modulation using dCas9 have also been reported, including the fusion of a dihydrofolate reductase destabilization domain to dCas9, which can provide chemical control over activation, enabling cellular reprogramming or differentiation (Balboa et al 2015). Light-inducible dCas9-based systems capable of providing optical control of gene expression provide another means for achieving conditional control of gene expression (Nihongaki et al 2015;Polstein and Gersbach 2015).…”
Section: Targeted Transcription Factors Tools For Modulating Gene Expmentioning
confidence: 99%
“…However, it remains to be demonstrated that transient transfection of vectors in PSCs can also mediate an increase in protein expression, given the difficulty of achieving the efficient plasmid delivery needed for endogenous gene targeting in difficult-to-transfect human iPSCs and the variability in the induction efficiency. In fact, evidence suggests that an increase in gene expression may be associated with an increase in protein translation [79,160,166]. Although correlation between mRNA abundance and protein synthesis is variable [220], achieving a sizeable -globin gene activation may translate into a higher level of protein expression.…”
Section: Resultsmentioning
confidence: 99%
“…Tandem repeats of VP16(n) (TAD) such as VP48 (n=3), VP64 (n=4), and VP160 (n=10) are commonly fused to a DNA binding domain in 23 order to target the activator to the gene of interest and promote its transcription [156]. VP96 (n=6) and VP192 (n=12) have been used infrequently [160]. ZFN, TALEN and Cas9 systems attached to such tandem VP16 repeats have been successfully used for transcriptional activation of various endogenous genes [79,161,162].…”
Section: Crispra-platforms For Gene Activationmentioning
confidence: 99%
See 2 more Smart Citations